Decreased ADAMTS-13 level is related to inflammation factors and risk stratification of acute lymphoblastic leukemia patients. Issue 7 (February 2017) - Liu, Chen; Zhao, Lei; Zhao, Jingzhong; Xu, Qinzhu; Song, Ying; Wang, Hui
Abstract : Abstract: As a kind of metalloprotease of the ADAMTS family, ADAMTS-13 is crucial for maintaining the normal size of von Willebrand factor. Reduced ADAMTS-13 had been reported in patients with both localized and disseminated malignancies. However, the expression and potential role of ADAMTS-13 in hematological malignancies remain unclear. In this research, we measured and compared ADAMTS-13 levels in plasma of 35 acute lymphoblastic leukemia (ALL) patients and 30 healthy controls and found that ALL patients possessed lower level of ADAMTS-13 than controls. Correlations between ADAMTS-13 and inflammation factors were calculated and ADAMTS-13 was negatively correlated with C-reactive protein and interleukin-1β. ALL patients with infections had lower level of ADAMTS-13 than patients without infections. In addition, high-risk ALL patients possessed lower ADAMTS-13 than patients at low risk. To conclude, ADAMTS-13 level is decreased in the plasma of ALL patients and the level of ADAMTS-13 is related to plasma inflammation factors and risk stratification of ALL patients, which could contribute to better understanding of the clinical significance of ADAMTS-13.